2021
DOI: 10.1021/acscatal.1c02238
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Metal–Ligand Cooperativity in Mn(II)-Catalyzed Hydroborations: Hemilabile SNS Ligand Enables Metal Hydride-Free Reaction Pathway

Abstract: A combined experimental and mechanistic study of the chemoselective hydroboration of carbonyls by the paramagnetic bis-amido Mn­[SMeNSMe]2 complex (1) is described. The catalyst allows for room-temperature hydroboration of carbonyls at low catalyst loadings (0.1 mol %) and reaction times (<30 min). A series of mechanistic studies highlight the significance of bifunctional amido bis­(thioether) ligand L to the success of the reaction, insight otherwise difficult to attain in paramagnetic systems. Kinetic studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Then, Gonsalvi and Kirchner et al showed that Mn­(I) complexes supported by PNP pincer ligand bearing N–H moieties in the backbone were able to bring about the efficient and selective hydroboration of CO 2 to methoxyboranes, which is one of the few examples of CO 2 borohydride catalyzed by the manganese-based catalyst . Similar works have been reported since then, and there are few studies on the mechanism of CO 2 hydroboration using manganese-based catalysts.…”
Section: Introductionmentioning
confidence: 58%
“…Then, Gonsalvi and Kirchner et al showed that Mn­(I) complexes supported by PNP pincer ligand bearing N–H moieties in the backbone were able to bring about the efficient and selective hydroboration of CO 2 to methoxyboranes, which is one of the few examples of CO 2 borohydride catalyzed by the manganese-based catalyst . Similar works have been reported since then, and there are few studies on the mechanism of CO 2 hydroboration using manganese-based catalysts.…”
Section: Introductionmentioning
confidence: 58%
“…In many cases for the hydroboration of carbonyls, the catalyst functions mainly as a Lewis acid, activating the carbonyl carbon for nucleophilic attack by the hydride of the borane reagent. A number of different transition metals have been used to catalyse this reaction, 430 including rhodium, 424,431 titanium, 401,402,[432][433][434][435][436][437][438] hafnium, 403 molybdenum, 325 silver, 406 cobalt, 169,[439][440][441][442] ruthenium, 404 palladium, 414,443 zinc, 412,413,444-450 iron, 415,[418][419][420]439,440,451,452 nickel, 409,410 manganese, 408,440,453 copper, 421,422 and yttrium. 454,455 Chiral diols combined with titanium(IV) complexes provide up to 99 : 1 enantiomeric ratios in the hydroboration of simple ketones with catecholborane.…”
Section: Ketonesmentioning
confidence: 99%
“…458 Baik and Baker collaboratively reported a similar transformation with bi-ligated Mn-amide complex Mn111 (Table 30, entry 5). 459 Although the scope of the reaction was not extensively studied, the catalyst was active under mild conditions, and a lower reaction time was required for complete conversion.…”
Section: Manganese-catalyzed Hydroelementation Reactionsmentioning
confidence: 99%